Sihir dan Hantu di Kalangan Masyarakat Aceh (Studi Terhadap Masyarakat Nisam Aceh Utara) - Safriadi, Safriadi (Al Mabhats : Jurnal Penelitian Sosial Agama, 2019)
This research is motivated by the existence of hostile communities to eliminate the lives of fellow members of the community by reason of magic. By some Acehnese people still pay great attention and belief in ghosts, magic practices and treatment procedures. This research is a field research (field research) that uses data collection methods of observation, interviews, and documentation. While the method of data analysis uses descriptive methods, and phenomenological methods. Descriptive method aims to describe the situation, and is used to determine the tradition of magic and understanding of ghosts carried out by the Nisam community. While the phenomenological method is an approach that studies the phenomena of society which are found from experience and reality in the field. The results of the analysis of this study indicate that most Nisam people in treating magic use two methods, namely the rukyah syar’iyah method and the magic method using the help of jinn. In a review of Islamic law, treatment of people affected by magic is carried out by the rukyah method in accordance with the advice of the Prophet. Very few Nisam people understand and do rukyah treatment methods, the majority still believe in treatment with the help of jinn. The term ghost in Islamic law is not mentioned. Ghost is another name for Jinn and Satan, Jinn and Satan are clearly mentioned in the Qur'an.